Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.7150/jca.15566
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin (BLM) Induces Epithelial-to-Mesenchymal Transition in Cultured A549 Cells via the TGF-β/Smad Signaling Pathway

Abstract: The epithelial-to-mesenchymal transition (EMT) is a crucial cellular event in wound healing, tissue repair, and cancer progression in adult tissues, with the interactions with numerous signals. In this study, we aimed to determine whether bleomycin (BLM), an agent that causes pulmonary fibrosis, induces the EMT of the alveolar epithelial cell line A549 and investigated the possible mechanisms. We examined the EMT involved changes in cell morphology, isoform switching of the fibroblast growth factor receptor 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…In previous studies, we demonstrated that bleomycin induces EMT partly through activating TGF-β/Smad/ESRP1 signaling [17,30]. However, the mechanism of bFGF in bleomycin-induced EMT is not clear.…”
Section: Bleomycin Induced Emt Partly Through Bfgf/pi3k/akt/esrp1 Sigmentioning
confidence: 94%
See 3 more Smart Citations
“…In previous studies, we demonstrated that bleomycin induces EMT partly through activating TGF-β/Smad/ESRP1 signaling [17,30]. However, the mechanism of bFGF in bleomycin-induced EMT is not clear.…”
Section: Bleomycin Induced Emt Partly Through Bfgf/pi3k/akt/esrp1 Sigmentioning
confidence: 94%
“…Increased expression of mesenchymal cell markers (Vimentin, α-SMA etc.) and decreased expression of epithelial cell markers (E-cadherin and cytokeratin) were found in TGF-β1-treated alveolar epithelial cells, A549 cells and bronchial epithelial cells [17][18][19]. In addition to its effect on the activation of Smad2/3, TGF-β also participates in other non-Smad signaling pathways to induce EMT, such as PI3K/Akt, ERK1/2 and MAPK [20,21], and can also alter cell behavior independently by stimulating nonreceptor protein tyrosine kinases, small GTP-binding proteins and MAP kinases [22,23].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Various evidences support TGF‐β1 to be the principle initiator, regulator, and propagator of fibrogenesis in scleroderma . BLM‐induced murine scleroderma is known to be associated with persistent activation of intracellular TGF‐β1/Smad signaling . Strong nuclear accumulation and phosphorylation of Smad2/3 takes place in resident skin fibroblasts following resolution of local inflammation.…”
Section: Discussionmentioning
confidence: 99%